Identification of a Novel Candidate Gene for Serrated Polyposis Syndrome Germline Predisposition by Performing Linkage Analysis Combined With Whole-Exome Sequencing. Issue 10 (October 2019) - Toma, Claudio; Díaz-Gay, Marcos; Soares de Lima, Yasmin; Arnau-Collell, Coral; Franch-Expósito, Sebastià; Muñoz, Jenifer; Overs, Bronwyn; Bonjoch, Laia; Carballal, Sabela; Ocaña, Teresa; Cuatrecasas, Miriam; Díaz de Bustamante, Aránzazu; et al.
Abstract : OBJECTIVES: Serrated polyposis syndrome (SPS) is a complex disorder with a high risk of colorectal cancer for which the germline factors remain largely unknown. Here, we combined whole-exome sequencing (WES) and linkage studies in families with multiple members affected by SPS to identify candidate genes harboring rare variants with higher penetrance effects. METHODS: Thirty-nine affected subjects from 16 extended SPS families underwent WES. Genome-wide linkage analysis was performed under linear and exponential models. The contribution of rare coding variants selected to be highly pathogenic was assessed using the gene-based segregation test. RESULTS: A significant linkage peak was identified on chromosome 3p25.2-p22.3 (maxSNP = rs2293787; LODlinear = 2.311, LODexp = 2.11), which logarithm of the odds (LOD) score increased after fine mapping for the same marker (maxSNP = rs2293787; LODlinear = 2.4, LODexp = 2.25). This linkage signal was replicated in 10 independent sets of random markers from this locus. To assess the contribution of rare variants predicted to be pathogenic, we performed a family-based segregation test with 11 rare variants predicted to be deleterious from 10 genes under the linkage intervals. This analysis showed significant segregation of rare variants with SPS in CAPT7, TMEM43, NGLY1, and FBLN2 genes (weighted P value > 0.007). DISCUSSION: Protein network analysis suggested FBLN2 as the most plausible candidate genes for germline SPS predisposition. Etiologic rare variants implicated in disease predisposition may be identified by combining traditional linkage with WES data. This powerful approach was effective for the identification of a new candidate gene for hereditary SPS.